Effect of catalpol on behavior and neurodevelopment in an ADHD rat model - Yuan, Haixia; Ni, Xinqiang; Zheng, Min; Han, Xinmin; Song, Yuchen; Yu, Minfeng (Biomedicine & pharmacotherapy, 2019)
•Catalpol attenuated hyperactivity and impulsiveness in SHR.•Catalpol improved spatial learning and memory of SHR.•Catalpol alleviated histomorphological changes in PFC and striatum of SHR.•Catalpol displayed neuroprotective effects and contributed to myelination.•Catalpol affected regulatory proteins implicated in PFC development. Studies suggest that abnormal neurodevelopment of prefrontal striatal circuits is implicated in the pathogenesis of attention deficit hyperactivity disorder (ADHD). In the present study, we investigated the effect of catalpol, an active ingredient of Rehmanniae radix preparata, which is the most frequently used Chinese medicinal herb for the treatment of ADHD, on behavior and neurodevelopment in spontaneously hypertensive rats (SHR). SHR were divided into SHR group (vehicle, i.g.), methylphenidate (MPH) group (2 mg/kg/day, i.g.), and catalpol group (50 mg/kg/day i.g.), and Wistar-Kyoto (WKY) rats were used as control group (vehicle, i.g.). Open Field Test (OFT) and Morris water maze (MWM) test were performed to assess the effect of catalpol on behavior. Results revealed that both catalpol and MPH treatment decreased average speed, time spent in the central area, rearing times, and central area visits, increased the immobility time of SHR in OFT, and increased number of visits to the annulus, and time spent in target quadrant in the MWM test. Hematoxylin and eosin (H&E) staining showed that catalpol reduced irregular neuronal arrangement, ruptured nuclear membranes, and resulted in disappearance of the nucleolus in the prefrontal cortex (PFC) and striatum of SHR. Moreover, immuno-fluorescent staining of NeuN and myelin basic protein (MBP) indicated that catalpol ameliorated neuronal loss and contributed to myelination. Finally, western blot and immunostaining analysis suggested that several regulatory proteins involved in PFC development were up-regulated by catalpol treatment, such as brain-derived neurotrophic factor (BDNF), cyclin-dependent kinase 5 (Cdk5), p35, fibroblast growth factor (FGF) 21 and its receptor (FGFR)1. Taken together, catalpol can effectively ameliorate hyperactive and impulsive behavior, improve spatial learning and memory in SHR, likely through the neurodevelopmental pathways. Nonetheless, whether catalpol could attenuate inattention in SHR and the pathway by which catalpol reduces neuronal loss remain to be further studied.